IMPROVING STUDENTS’ ABILITY TO COMPREHEND SPOOF TEXT USING RECIPROCAL TECHNIQUE - Wimanistya, Erla; Apriliaswati, Rahayu; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aimed to improve students’ ability to comprehend spoof text using reciprocal technique. The writer applied classroom action research in three cycles. The subjects of this research were the eleventh grade students, science 2 class, in SMA Negeri 6 Pontianak, academic year 2013/2014. There were 36 students in that class, yet only 35 who came in the whole cycles were analyzed. The data was collected using observation checklist, field notes and written test. The technique applied in this research is the reciprocal technique which is consisted of predicting, questioning, clarifying and summarizing. It revealed that the students improved their score of the test. Students’ average score in the first cycle was 64 which then improved in the second (77) and third cycles (83.1). There are three main features of the spoof text analyzed; main idea and detailed information, language features identification and the twist. Key words: Reciprocal, Spoof text, Reading Comprehension Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan siswa untuk memahami teks spoof menggunakan teknik resiprokal. Peneliti menggunakan Penelitian Tindakan Kelas dalam tiga siklus. Subyek Penelitian ini adalah siswa kelas 11 Ipa 2 SMA Negeri 6 Pontianak TA 2013/2014. Ada 36 siswa, namun hanya 35 siswa yang mengikuti keseluruhan siklus yang akan dianalisis. Data dikumpulkan menggunakan ceklis observasi, catatan lapangan dan tes tertulis. Teknik yang diaplikasikan di penelitian ini adalah teknik resiprokal, yang terdiri atas memprediksi, bertanya, klarifikasi dan menyimpulkan. Hasil Penelitian menunjukkan bahwa nilai siswa meningkat di tiap siklus. Rerata nilai siswa di tiap siklus adalah 64, 77, dan 83.1. Ada tiga hal utama dari teks spoof yang menjadi poin penelitian, yaitu ide pokok dan informasi detail, identifikasi fitur bahasa, dan twist dari teks spoof. Kata kunci: Resiprokal, Teks Spoof, Pemahaman Membaca